A contemporary overview of factors hindering the improvement of maternal health literacy among mothers in South Asia: a systematic review and a thematic analysis - Jayawardhana, K. G. L. A. N. S; Srihari, M. (International Journal Of Community Medicine And Public Health, 2025)
In South Asia, maternal health remains an important public health challenge and poor maternal health literacy (MHL) of mothers has been identified as a root cause of maternal deaths. However, systematic literature reviews conducted to identify ‘contemporary’ factors hindering the improvement of MHL among mothers in South Asian countries are rare. Hence, this systematic review aims to identify the contemporary factors that impede the MHL among mothers in South Asia. Research articles for the review were selected using preferred reporting items for systematic reviews and meta-analysis (PRISMA). Initially, 264 articles were retrieved from 11 prominent publishing databases, including Taylor and Francis, Elsevier, and Sage. Of these, 21 articles published on six South Asian countries between January 2020 and May 2025 were selected, considering inclusion and exclusion criteria. Nutbeam’s health-literacy classification was used to direct the thematic analysis. As findings, ‘lack of formal education of mothers’, ‘cultural barriers’, ‘misconceptions regarding formal healthcare sector’, ‘low maternal age’, ‘less exposure to media’, ‘less access to digital technology and low digital literacy’, ‘low family income’, ‘family structures’, ‘work obligations’, ‘partner’s involvement’, ‘area of residence’, ‘shyness and discomfort of sharing gynecological issues’, ‘influence of the religion’, and ‘gender inequality in decision-making’ were recognized. These findings provide an overview of reasons behind low MHL among mothers in socio-culturally diverse South Asia, and highlight the importance of overcoming such factors through practical implications to contribute to achieving low maternal mortality rates as per UN Sustainable Development Goal 3.1, ‘reducing the global maternal mortality ratio’ by 2030.